Polizeisoziologie Grundlagen, Forschungen und Lehre - Hörl, Josef (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
For students and those interested in police sociology, an introductory basic text is now available. In ten chapters, the authors summarise the location of police sociology among academic disciplines, describe the police and their development, and analyse their relationship to the public. They also discuss the role of women and people with immigrant backgrounds in a traditionally male-dominated profession. Research on police sociology, such as dealing with crowds, and personal teaching experiences-of sociology for police officers and police sociology for students at the University of Vienna, for example-conclude the book.